Geronimo Stilton Spacemice #05 : Rescue Rebellion - Stilton, Geronimo (Scholastic Inc., 2015)
Geronimo Stiltonix and his crew head to the planet Jurassix to warn its inhabitants of a giant comet heading straight toward them. But the creatures there turn out to be ferocious, dinosaur-like beasts who like to eat rodents. Squeak. Can the spacemice save these aliens and still make it out alive.